Fungsi dan perwujudan identitas nasional sebagai fondasi bangsa - Maulana, Gusti Fitra (Maliki Interdisciplinary Journal, 2025)
This research aims to examine the important role of Indonesia’s national identity and the challenges it faces amid the influence of globalization. Indonesia’s national identity, which is manifested through various symbols such as the Indonesian language, the Red and White Flag, the National Anthem “Indonesia Raya”, Garuda Pancasila, and the motto “Bhinneka Tunggal Ika”, has a crucial role in strengthening the unity of a nation consisting of various ethnicities and cultures. However, along with the progress of the times and the entry of the influence of globalization, there are various challenges that threaten the preservation of national identity, such as the dominance of foreign cultures, the decline in love for domestic products, and changes in language use patterns. This research uses a qualitative approach by examining various references that discuss Indonesia’s national identity and the impact of globalization on it. The findings show that deviations from Indonesia’s national identity, which are influenced by internal and external factors, can be reduced through improving national education, preserving local culture, and strengthening national integrity. This research emphasizes the importance of the active role of the community and the government in maintaining and strengthenig Indonesia’s national identity in order to remain relevant and strong amidst the growing globalization.